Conditions Monetaires Et Croissance Economique En Zone Cemac (Global Journal of Management and Business Research, 2019)
The objective of this study is to track the monetary policy stance in CEMAC zone with GDP as target variable using a real size. The construction of reel monetary condition index use heterogeneous macropanels VAR approach with individual specification proposed par Fabio and al (2013). The interindividual cointégration test confirm the long term relationship between GDP, real short run interest rate, real effective exchange rate and credit to economy making possible the combination of those instruments to forecast growth. But the result of intraindividual cointegration remains lukewarm compromising the possibility to combine the instruments above-mentioned in a single synthetic indicator for each country in CEMAC zone. The estimation of model parameters has been done through pooled mean group in Blackburn and Fran (2007) way. The construction of real ICM uses Canada Bank approach. One finds that real ICM is determined mainly by real effective exchange rate, then credit to economy and lastly the real short run interest rate. The construction of ICM must be included among the large range of indicators used by central bank to forecast growth in CEMAC zone.
Keywords: monetary policy; reel monetary condition index; heterogeneous macropanels; cointegration